Processos de significação em contraste: violência contra as mulheres no Brasil e em Cabo Verde - Miriam Steffen Vieira (Ciências Sociais Unisinos)
This paper aims at presenting a brief overview of the construction process of legalities in the field of violence against women in Brazil in order to suggest, then, some contrastive elements regarding this process in Cape Verde. The main goal is to identify meanings that take gender into policy making processes. In the case of Cape Verde, ethnographic data were collected at different times of public discourse on the implementation of the law that criminalized violence based on gender, in January 2011.